Gerakan Perempuan Abad 19-20 - Amanda Syakiyah Rahmanita (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
Women's organizations are formed from among women themselves, because of the self-awareness of women. The steps taken by women figures throughout history are proof of the seriousness of Indonesian women to lay the foundation for the women's movement in the name of humanity and social justice. Fujinkai was one of the organizations that were allowed to remain standing during the Japanese occupation. This article will discuss the women's movement that emerged in the 19-20 centuries, by explaining the role of several women at that time. This discussion is limited temporally, namely in the pre-independence period only. In writing articles, the author uses the historical method by going through a series of stages such as gathering sources (heuristics), verification (historical criticism, validity of sources), interpretation, and writing. From this research resulted in several discussions, namely: 1) Women and the nature of humanity, 2) Women's movements in the colonial period, 3) Women during the Japanese colonial period.